(untitled) (MMIT Proceedings, 2024)
Modern tools and technologies play a crucial role in the educational process, particularly when it comes to teaching Python programming. This article will provide an overview of how these advanced tools and technologies are used in the context of learning Python. The article will explore various aspects of modern education, including interactive online platforms, integrated development environments (IDEs), such as PyCharm and Jupyter Notebook. It will also discuss cloud services for app development and deployment, such as GitHub and Heroku, as well as online courses, video tutorials, visualization tools, and machine learning and data analysis services. Additionally, task and project management systems will be discussed. This review aims to provide a better understanding of the significance and importance of these modern technologies in today’s education system and their impact on the efficiency and effectiveness of learning Python.